2014
DOI: 10.1007/s10096-014-2249-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of carbapenem-resistant Enterobacteriaceae at a tertiary care laboratory in Mumbai

Abstract: Carbapenem-hydrolyzing β-lactamases are increasingly reported worldwide, leading to therapeutic failure. In an era where the drug development pipeline is stagnant, it is crucial to preserve current classes of antibiotics to help fight against infection caused by multidrug-resistant organisms (MDROs), by practicing a rational approach for the use of antibiotics. Identifying the mechanisms of resistance gives us much needed insights in this field. A total of 113 consecutive, non-duplicate carbapenem-resistant cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 21 publications
6
40
0
2
Order By: Relevance
“…Carbapenem resistance rates in Enterobacteriaceae have been more variable than those in CRAB in India, but longitudinal studies have shown dramatic increases in resistance rates over time (10,53,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). NDM remains consistently the major carbapenemase found in Enterobacteriaceae in that country (72). CP-CRE have been identified in the environment in the community since 2010 (14,73), likely as a consequence of sanitation issues.…”
Section: South Asiamentioning
confidence: 99%
“…Carbapenem resistance rates in Enterobacteriaceae have been more variable than those in CRAB in India, but longitudinal studies have shown dramatic increases in resistance rates over time (10,53,(62)(63)(64)(65)(66)(67)(68)(69)(70)(71). NDM remains consistently the major carbapenemase found in Enterobacteriaceae in that country (72). CP-CRE have been identified in the environment in the community since 2010 (14,73), likely as a consequence of sanitation issues.…”
Section: South Asiamentioning
confidence: 99%
“…KPCs were initially detected in a clinical isolate in 1996 in North Carolina; since then, 19 variants have been discovered (21)(22)(23)(24). KPC has been found in a variety of Enterobacteriaceae, including Klebsiella spp., Escherichia coli, Enterobacter spp., Citrobacter spp., Morganella spp., Serratia marcescens (25)(26)(27)(28)(29), Raoultella spp. (30), Kluyvera (31), and Salmonella (32), and in non-Enterobacteriaceae such as Aeromonas (33), Pseudomonas, and Acinetobacter baumannii (34).…”
Section: Current Status Of Carbapenemasesmentioning
confidence: 99%
“…An alarming finding from a molecular characterization study of carbapenem-resistant Enterobacteriacea in Mumbai, West India, revealed that 18.5% (21/113) of the clinical isolates investigated possessed dual carbapenemase genes [34]. Moreover, recently a series of 24 cases of colistin-resistant Klebsiella pneumoniae has been reported from a new oncology center at Kolkata.…”
Section: Surveillance and Epidemiologymentioning
confidence: 99%